Capsaicin—the major bioactive ingredient of chili peppers: bio-efficacy and delivery systems. Issue 4 (4th April 2020) - Lu, Muwen; Chen, Chengyu; Lan, Yaqi; Xiao, Jie; Li, Run; Huang, Junqing; Huang, Qingrong; Cao, Yong; Ho, Chi-Tang
Abstract : The mechanisms of bio-efficacy of capsaicin and delivery systems with enhanced bioavailability were reviewed. Abstract : Capsaicin is the primary bioactive substance in red chili peppers, which produces the pungent flavor. During the past few decades, pharmacological benefits of capsaicin and its underlying mechanisms have been examined extensively. In this paper, major biological efficacies of capsaicin are reviewed, including analgesic, antioxidant, anti-inflammatory, anti-cancer, anti-obesity, cardio-protective, and metabolic modulation effects. Novel delivery systems, such as liposomes, micelles, micro/nano-emulsions, colloidal capsules and solid nanoparticles, for enhancing the oral bioavailability of capsaicin are also evaluated depending on the stability, encapsulation efficiency and biological properties. This review provides a theoretical basis for capsaicin to be further developed into a multi-functional ingredient with health-promoting functions in the nutraceutical industry.